Interactive impact of potassium and arbuscular mycorrhizal fungi on the root morphology and nutrient uptake of sweet potato (Ipomoea batatas L.) - Yuan, Jie; Shi, Kun; Zhou, Xiaoyue; Wang, Lei; Xu, Cong; Zhang, Hui; Zhu, Guopeng; Si, Chengcheng; Wang, Jidong; Zhang, Yongchun (Frontiers in Microbiology, 2023)
Sweet potato is a typical ‘potassium (K) -favoring’ food crop, and strongly dependent on arbuscular mycorrhizal fungi (AMF). Recent studies show the importance of K and AMF to morphology optimization and nutrient uptake regulation of sweet potato, meanwhile the interaction exists between K and K use eﬃciency (KIUE) in sweet potato. To date, only few studies have shown that AMF can improve plant K nutrition, whether the benefits conferred by AMF on plant are related to K remains unclear. In this study, low-KIUE genotype ‘N1’ and high-KIUE genotype ‘Xu28’ were used as experimental sweet potato; Funneliformis mosseae (FM) and Claroideoglomus etunicatum (CE) were used as experimental AMF. In a pot experiment, plants ‘N1’ and ‘Xu28’ were inoculated with FM or CE, and applied with or without K fertilizer to uncover the effects of K application and AMF inoculation on root morphology and nutrient absorption of sweet potato during their growing period. Results demonstrated that AMF inoculation-improved root morphology of sweet potato highly relied on K application. With K application, AMF inoculation significantly increased root tip number of ‘N1’ in the swelling stage, and optimized multiple root morphological indexes (total root length, root surface area, root volume, root diameter, root branch number and root tip number) of ‘Xu28’, and CE had the best optimization effect on root morphology of ‘Xu28’. In addition, CE inoculation significantly promoted root dry matter accumulation of ‘Xu28’ in the swelling and harvesting stages, and coordinated of aerial part and root growth of ‘Xu28’, reduced the dry matter to leaf and petiole, be beneficial to dry matter allocation to the root under conditions of K supply. Another promising finding was that CE inoculation could limit K allocation to the aboveground and promote root K accumulation of ‘Xu28’ under the condition with K application. The above results lead to the conclusion that K and CE displayed a synergistic effect on root development and K acquisition of high-KIUE ‘Xu28’. This study could provide theoretical basis for more scientific application of AMF in sweet potato cultivation, and will help to further clarify the outcomes of plant-K-AMF interactions.